Green transformation of airport architecture through biophilic design: A comparative study of Changi, Munich, and Banyuwangi - Isdanto Rahusodo (Journal of Placemaking and Streetscape Design, 2026)
Background: Modern airports play a vital role in the global transportation network, but they also contribute greatly to the environmental crisis due to high energy consumption and carbon emissions. This study examines the transformation of green architecture through the application of biophilic design as a mitigation strategy at three international airports (Changi, Munich, and Banyuwangi). Methods: A comparative case study approach with mixed methods (architectural observation, document analysis, and user surveys) was used to evaluate the integration of biophilic elements in an effort to improve energy efficiency, resource management, and adaptation to local climatic and cultural conditions. Findings: The results of the study show that the adaptation of biophilic design that takes into account local wisdom and local climate is able to optimize the performance of the airport environment, significantly reduce energy consumption and carbon emissions, and improve the psychological comfort of users. In addition, the application of natural elements such as indoor gardens, artificial waterfalls, green roofs, and natural ventilation is proven to create a healthier and more attractive space atmosphere. Conclusion: These findings enrich the discourse on sustainable architecture, affirm the relevance of biophilic design in facing the challenges of the global environmental crisis, and provide practical recommendations for the development of more environmentally friendly transportation infrastructure. Novelty/Originality of this article: This study offers originality by demonstrating how biophilic design, grounded in local wisdom and climatic context, can transform large-scale airport infrastructure into sustainable, human-centered public spaces with strong cultural identity, while simultaneously enhancing ecological performance and user well-being.